2010
DOI: 10.1007/s00125-010-1967-6
|View full text |Cite
|
Sign up to set email alerts
|

Insulin promoter DNA methylation correlates negatively with insulin gene expression and positively with HbA1c levels in human pancreatic islets

Abstract: Aims/hypothesisAlthough recent studies propose that epigenetic factors influence insulin expression, the regulation of the insulin gene in type 2 diabetic islets is still not fully understood. Here, we examined DNA methylation of the insulin gene promoter in pancreatic islets from patients with type 2 diabetes and non-diabetic human donors and related it to insulin expression, HbA1c levels, BMI and age.MethodsDNA methylation was analysed in 25 CpG sites of the insulin promoter and insulin mRNA expression was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
180
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(197 citation statements)
references
References 20 publications
(23 reference statements)
14
180
1
2
Order By: Relevance
“…These are chemical alterations of the DNA that affect gene function and expression without changing the DNA sequence (20 -22). Recent studies by our group and others' demonstrate that epigenetic modifications, including DNA methylation and histone modifications, in human pancreatic islets influence gene expression, islet function, and most likely the pathogenesis of T2D (23)(24)(25)(26)(27). To our knowledge, it has not yet been shown that FAs regulate histone modifications in pancreatic ␤-cells.…”
Section: Type 2 Diabetes (T2d)mentioning
confidence: 99%
“…These are chemical alterations of the DNA that affect gene function and expression without changing the DNA sequence (20 -22). Recent studies by our group and others' demonstrate that epigenetic modifications, including DNA methylation and histone modifications, in human pancreatic islets influence gene expression, islet function, and most likely the pathogenesis of T2D (23)(24)(25)(26)(27). To our knowledge, it has not yet been shown that FAs regulate histone modifications in pancreatic ␤-cells.…”
Section: Type 2 Diabetes (T2d)mentioning
confidence: 99%
“…For static measurements of insulin release, groups of 8 10 islets were incubated at 37 0 C for 1 h in 300 μl of the same buffer containing 3.3 or 16.7 mM glucose. Released insulin was measured in the buffer by radio immunoassay (RIA) as described [16]. Insulin content was extracted by acid ethanol and analyzed by RIA as previously described [16].…”
Section: Insulin Secretion and Contentmentioning
confidence: 99%
“…Released insulin was measured in the buffer by radio immunoassay (RIA) as described [16]. Insulin content was extracted by acid ethanol and analyzed by RIA as previously described [16].…”
Section: Insulin Secretion and Contentmentioning
confidence: 99%
“…1 Insulin resistance (IR) is produced as soon as the pancreatic b-cells cannot compensate a reduced insulin function, leading to elevated circulating glucose levels. 2 Insulin inhibits gluconeogenesis in the liver and reduces lipolysis in adipose tissue.…”
Section: Introductionmentioning
confidence: 99%